PEMBELAJARAN IPS BERBASIS LITERASI DIGITAL - Muhammad Nur (CV. ADIBA ASIHA AMIRA, 2023)
The results of this study indicate that; 1) Social studies learning based on digital literacy in schools increases the digital literacy level of the majority of students at the medium level. This indicates that the majority of students have an intermediate level in using digital media, know the functions of digital media in more depth, are able to operate digital media more complexly, know how to obtain and evaluate the information needed, can evaluate information search strategies, and have been active in production. content and participation in digital media. Then refer to the 9 elements of digital literacy with the lowest score on the repurposing content element. This means the low ability of students to use or combine existing content to produce creative new content. 2) Indicators of the school-based digital literacy movement according to the Ministry of Education and Culture, the school-based digital literacy movement also includes the application and utilization of digital literacy not only in Social Sciences but also in several subjects (Indonesian, English, Mathematics, and Natural Sciences) at the initiative of subject teachers. In addition, there is already a teacher's understanding of the concept of digital literacy, which places more emphasis on cognitive aspects.